Altered Fractional Amplitude of Low-Frequency Fluctuation in Major Depressive Disorder and Bipolar Disorder - Qiu, Yan; Yang, Min; Li, Sujuan; Teng, Ziwei; Jin, Kun; Wu, Chujun; Xu, Xuelei; Chen, Jindong; Tang, Hui; Huang, Jing; Xiang, Hui; Guo, Wenbin; et al. (Frontiers in Psychiatry, 2021)
Background: Discriminating between major depressive disorder (MDD) and bipolar disorder (BD) remains challenging and cognition deficits in MDD and BD are generally recognized. In this study, the fractional amplitude of low-frequency fluctuation (fALFF) approach was performed to explore neural activities and cognition in first-episode, drug-naïve BD and MDD patients, as well as the relationships between altered fALFF values and clinical or psychometric variables. Methods: A total of 20 BD patients, 23 MDD patients and 40 healthy controls (HCs) completed clinical assessments and resting-state functional magnetic resonance imaging (rs-fMRI) scans in this study. The rs-fMRI data were analyzed by fALFF method and Pearson correlation analyses were performed between the altered fALFF values and clinical variables or cognition. Support vector machine (SVM) was adopted to identify the three groups from each other with the abnormal fALFF values in the brain regions obtained by group comparisons. Results: (1) The fALFF values were significantly different in the frontal lobe, temporal lobe, and left precuneus among three groups. In comparison to HCs, BD showed increased fALFF values in the right inferior temporal gyrus (ITG) and decreased fALFF values in the right middle temporal gyrus, while MDD showed decreased fALFF values in the right cerebellar lobule Ⅳ/Ⅴ. In comparison to MDD, BD showed decreased fALFF values in bilateral posterior cingulate gyrus and the right cerebellar lobule Ⅷ/Ⅸ. (2) In BD group, a negative correlation was found between the fALFF values in the right ITG and years of education, and a positive correlation was found between the fALFF values in the right cerebellar lobule Ⅷ/Ⅸ and visuospatial abilities. (3) The fALFF values in the right cerebellar lobule Ⅷ/Ⅸ may have the ability to discriminate BD patients from MDD patients, with sensitivity, specificity and accuracy all over 0.70. Conclusions: Abnormal brain activities were observed in BD and MDD, and were related with cognition in BD patients. The abnormality in the cerebellum can potentially identify BD from MDD patients.